Vowel Raising in Nkpor Dialect: A Pattern of Sound Change - Mbah, Evelyn Ezinwanne; Okeke, Chukwuma Onyebuchi (Linguistik Online, 2014)
This paper explores a pattern of phonological change known as vowel raising in the Nkpor dialect of the Igbo language. Using a corpus of conversational Nkpor speech collected from the respondents through tape-recording, we presented data from an authority analysis of the vowels and auditory data of vowel raising. The data support three main claims. First, the voiced palatal nasal /ɲ/ is elided. It claims that in a word consisting of two root verbs, the initial verb root contains any consonant and any vowel, and the second verb root contains the voiced palatal nasal /ɲ/ and a mid front vowel /e/, then, the voiced palatal nasal is elided. Second, after the elision, the mid vowel /e/ of the second verb is raised to a high front vowel /i/ or /ɪ/, agreeing with the vowel harmony rule. Third, Nkpor dialect goes beyond the raising of only vowels of the second verb. It further raises vowels of the first verb which are not high. The much more rapid loss of the voiced palatal nasal /ɲ/ and the consequent raising of the vowels are plausibly attributed to rapid speech, especially in construction and some sociolinguistic factors.